Dopplervelocimetria da artéria oftálmica em gestantes pré-eclâmpticas com recém-nascidos portadores de restrição de crescimento - Freitas, Marta Alves de [UNESP] (2015)
Introduction: Among hypertensive disorders that affect pregnancy, preeclampsia (PE) is the leading cause of mortality in short and long-term maternal morbidity and also perinatal complications such as premature birth, growth restriction and death. The examination of eye reflects changes arising from systemic vasospasm, a basic change in the disease pathophysiology. The Doppler of ophthalmic arteries is a reproducible and noninvasive, thus becoming an objective method that sets the manifestations of hypertension among themselves, enhances the understanding of the preeclampsia pathophysiology and identifies the severity of the disease, directly related to the central nervous system compromising. Objective: To identify if there is a relationship between changes in the Doppler of the ophthalmic artery of pregnant women with PE and the occurrence of fetal growth restriction. Subjects and Methods: Across sectional study in a population of 75 pregnant women with a diagnosis of PE, who had pregnancy resolution at Regional Hospital of Gama - Federal District and whose newborns were classified according to their weight for gestational age (SGA - small for gestational age and not SGA) according to Lubchenco table. The dopplervelocimetry of the ophthalmic artery was performed in 17 Nemio Toshiba equipment with linear transducer in the frequency of 10 MHz and, the following parameters were determined: resistance index (RI), pulsatility index (PI), systolic velocity peak(SVP), end-diastolic velocity (EDV) and velocity ratio peak (VRP). Statistical analyses were performed using ANOVA and Chi-square test. The results were considered statistically significant with p values <0.05. Results: Analysis of maternal clinical characteristics, according to the newborns classification (Not SGA and SGA), showed no significant difference in maternal age (27.7+6.8 years vs 29.5+7, 4 years), parity (48.2% vs 50%) and the rate of cesarean delivery (84.7% vs 100%). ...